Improvement of high‐temperature stability of PIP SiCf/SiC material through in situ grown BNNTs. Issue 6 (29th July 2021) - Xu, Shenwei; Pi, Huiling; Wu, Pengfei; Huang, Xiaozhong; Shi, Yuan; Li, Longbiao; Yang, Haitang
Abstract: In this paper, the effect of in situ grown boron nitride nanotubes (BNNTs) and preparation temperature on mechanical behavior of PIP (Precursor Infiltration and Pyrolysis) SiCf /SiC minicomposites under monotonic and compliance tensile is investigated. In situ BNNTs are grown on the surface of SiC fibers using ball milling–annealing process. Composite elastic modulus, tensile strength, fracture strain, tangent modulus, and loading/unloading inverse tangent modulus (ITM) are obtained and adopted to characterize the mechanical properties of the composites. Microstructures of in situ grown BNNTs and tensile fracture surfaces are observed under scanning electronic microscopic (SEM). For SiCf /SiC minicomposites with BNNTs, the elastic modulus, tensile strength, and fracture strain are all lower than those of SiCf /SiC minicomposites without BNNTs, mainly due to high preparation temperature and the oxidation of the PyC interphase during the annealing process. Tensile stress–strain curves of SiCf /SiC minicomposites with and without BNNTs are predicted using the developed micromechanical constitutive model. The predicted results agreed with experimental data. This work will provide guidance for predicting the service life of SiCf /SiC composite materials and may enable these materials to become a backbone for thermal structure systems in aerospace applications.